2021
DOI: 10.1016/j.cpha.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Wound Infections

Abstract: The work of Louis Pasteur, Joseph Lister, and Robert Koch in the late nineteenth century has informed the role of infection on surgical outcomes and ultimately served as the foundation for the transformation of surgical medicine. Louis Pasteur was a French scientist whose studies in fermentation, anthrax, silkworm disease, chicken cholera, and rabies led to the development of the germ theory of fermentation and subsequently the germ theory of disease. 1-3 In his early fermentation studies, he proposed that mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We have encompassed all experimental investigations published from 1990 16 to the current date, delving into the application of ML in evaluating surgical wounds. Exclusionary criteria were applied, eliminating studies that did not meet the following specifications 1 : the absence of full text, 2 studies predominantly grounded ML in all parts of surgeries, 3 those neglecting the assessment of the wound, 4 articles covering reviews, guidelines or conference proceedings and 5 duplications found across databases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have encompassed all experimental investigations published from 1990 16 to the current date, delving into the application of ML in evaluating surgical wounds. Exclusionary criteria were applied, eliminating studies that did not meet the following specifications 1 : the absence of full text, 2 studies predominantly grounded ML in all parts of surgeries, 3 those neglecting the assessment of the wound, 4 articles covering reviews, guidelines or conference proceedings and 5 duplications found across databases.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical procedures, given their complexity, can give rise to various complications 1 . In this regard, complications such as postoperative wound infections, a common consequence of many surgeries, can lead to unfavourable surgical outcomes like prolonged hospitalization and mortality 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation